Optimization of CABRI power transients with the SPARTE code and the URANIE uncertainty platform. (September 2018) - Clamens, O.; Hudelot, J-P.; Blaise, P.; Lecerf, J.; Duc, B.; Garnier, Y.; Biard, B.
Abstract: One goal of the SPARTE code is to be used as a guide to select the experiments design parameters for future CABRI power transients. This paper focuses on methods for optimizing a specific CABRI power transient (FWHM (Full Width at Half Maximum) ≃30 ms, Deposited energy ≃130 MJ) using the target characteristics of the pulse. The selection of a method may help the experimentalists and the operation team to minimize the number of "white" power transients to perform before the final test with the fuel sample. The optimization can lead to different results, that can be ranked according to their projected uncertainties. Different optimization methods are tested and compared in this paper. The Subplex method based on reiterations of the Nelder-Mead algorithm (simplex method) was selected for its high precision. Indeed, the CABRI power transients are not completely reproducible and present some uncertainties linked to the test parameters. This article focuses on the uncertainties propagation in order to identify and select the parameters that minimize the output uncertainties. The results are very satisfactory and lead to several optimized scenarios that will be tested during the next qualification test campaign.